O lugar da mulher no quilombo Kalunga - Godinho, Tereza Martins (2008)
This research was done at, located at the cities of Cavalcante, Teresina and Monte Alegre, northeast of the State of Goiás. As from references of Anthropological Theory, tried to describe this Hiding-place of fugitive Negro Slaves and its people considering their caracteristics of identity, of culture, social, economical and historical. Investigated and analyzed above all the role of women, through their cultural atitudes and routine, foccusing the relations they have with themselves, with their partners, with their group and with their past, trying to understand the meaning of " being a woman" in this context. The method used was open country work, preceded of bibliographical survey associated to research of documents